Renal denervation- its current status & future prospects for management of Hypertension - Sreenivas Kumar Arramraju; Rama Krishna Janapati (Archives of Clinical Hypertension - Peertechz Publications, 2020)
Hypertension is one of the major contributing factor for global burden of cardiovascular morbidity and mortality. It was estimated that 1.13 billion people were affected worldwide and most of them are residing in low and middle income countries [1]. Hypertension was strongly associated with coronary artery disease, cerebrovascular events and peripheral artery disease.